A rare clinical case of pulmonary artery sarcoma - G. R. Bikbaeva; A. N. Kovalskaya; A. P. Rodin; G. V. Salamov; T. V. Pavlova; D. V. Duplyakov (Столичная издательская компания, 2024)
Pulmonary artery sarcoma (PAS) is a malignant and very rare tumor with frequent misdiagnosis. A rare clinical case with this pathology is presented. The patient had daily fever for 6 months, he was examined in various hospitals, but the cause of fever could not be determined. In our hospital, echocardiography revealed a mass in the left pulmonary artery (PA) with obstruction. CT-angiopulmonography showed a filling defect in the left PA, blocking the lumen of the artery by 90%. According to histopathology, the patient was diagnosed with pulmonary artery sarcoma. Subsequently, the following was performed: thrombendarterectomy from the pulmonary artery, combined pneumonectomy on the left side, suturing of the secondary atrial septal defect, followed by 3 courses of monochemotherapy with paclitaxel. After 1 year and 9 months, due to disease progression the patient died. The prognosis of PAS depends on early diagnosis, so doctors should be aware of this disease and use the best treatment options.